2022
DOI: 10.1111/joor.13335
|View full text |Cite
|
Sign up to set email alerts
|

The utility of telemedicine in orofacial pain: Guidelines for examination and a retrospective review at a hospital‐based practice

Abstract: Following the onset of the COVID-19 pandemic in 2020, hospitals and dental clinics temporarily limited their patient services and instead relied upon telemedicine to provide consultations and follow-up visits remotely. Various medical and dental specialties, including oral and maxillofacial surgery and oral medicine, have since adapted by providing care remotely and continue to do so. [1][2][3] However, the use of telemedicine in orofacial pain for examination, evaluation, and diagnostic utility has not been w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…Thus, it is reasonable to think that TD has to date, expressed only a small part of its true potential, and that in the near future most of the dental treatments will be able to be performed remotely. Unfortunately, while a great number of works has established the effectiveness of TD regarding oral malignancies [ 37 ], orofacial pain [ 38 ] and MRONJ diagnosis [ 39 ], management of patients with temporo-mandibular disorders [ 40 ] and oral surgery follow-up [ 41 , 42 ], there is a full lack of reports describing dental interventions performed remotely. Contrary to general surgery, no devices for this kind of practice have been developed and a great effort will be necessary for realizing technologic instruments as well as to create a new mindset among the practitioners.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Thus, it is reasonable to think that TD has to date, expressed only a small part of its true potential, and that in the near future most of the dental treatments will be able to be performed remotely. Unfortunately, while a great number of works has established the effectiveness of TD regarding oral malignancies [ 37 ], orofacial pain [ 38 ] and MRONJ diagnosis [ 39 ], management of patients with temporo-mandibular disorders [ 40 ] and oral surgery follow-up [ 41 , 42 ], there is a full lack of reports describing dental interventions performed remotely. Contrary to general surgery, no devices for this kind of practice have been developed and a great effort will be necessary for realizing technologic instruments as well as to create a new mindset among the practitioners.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Исследователями из США [55] проведен ретроспективный обзор всех новых телемедицинских консультаций со 2 апреля 2020 г. по 29 марта 2021 г. у пациентов с ОФБ. Всего авторами были проанализированы данные 270 новых пациентов.…”
Section: телемедицинская диагностика в период пандемииunclassified
“…В дальнейшем 146 пациентов обратились в клинику для амбулаторного наблюдения, при этом 78,8% имели точный телемедицинский диагноз. Сложность дифференциальной диагностики жевательной миофасциальной боли и артралгии ВНЧС была наиболее распространенной причиной неточности во время телемедицинской диагностики [55].…”
Section: телемедицинская диагностика в период пандемииunclassified
“…The study shows that Teleconsultation for patients with Orofacial Pain (OFP) provides a tool for diagnosis and can help expedite treatment for patients who face challenges presenting for an in-office consultation. 11 …”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study was published in 2021 by Al-Khalifa, K. and AlSheikh, R. in Saudi Arabia, based on 286 dental professionals who participated in the study. 11 The authors obtained a list of dental professionals from the Saudi Commission for Health Specialties database and randomly emailed them for participation. The results showed that most participants anticipated that Teledentistry would improve dental practice and the readiness of dental professionals to be engaged in Teledentistry.…”
Section: Introductionmentioning
confidence: 99%